Air Entrainment and Gas Transfer in Wave Breaking Events - S. Di Giorgio; S. Pirozzoli; A. Iafrati (Geophysical Research Letters)
Abstract We investigate gas transfer processes occurring at the air‐water interface of progressive water waves using high‐fidelity numerical simulations. Waves with varying initial steepness, including regular wave patterns, mild spilling, and intense plunging breakers are examined. A two‐phase solver is employed to model exchange processes enabling precise estimation of the air‐water interface area and gas transfer velocity, achieving an accuracy unattainable in experiments. We show that the volume of gas transferred across the air‐water interface increases significantly with the amount of air entrained due to wave breaking, peak values in the transfer velocity being concurrent with peaks in energy dissipation rate and air entrainment. The gas transfer velocity is observed to scale approximately as the one‐fourth power of the energy dissipation rate, consistent with previous theoretical predictions. The present findings can help reduce the substantial uncertainty associated with the parametrization of fundamental natural processes, such as CO2 absorption by the oceans.